Sistem Informasi Perpustakaan Menggunakan Algoritma Pencarian Knuth Morris Paratt (KMP) dalam Pencarian Judul Buku (Studi Kasus: Perpustakaan Universitas Alma Ata) - Sumanto, Sumanto; Gutama, Deden Hardan; Wijaya, Dhina Puspasari; Pramuntadi, Andri (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to develop an Online Public Access Catalog (OPAC) website at the Alma Ata University library using the Knuth Morris Pratt (KMP) algorithm as the book title search method. The research method used is quantitative, with a focus on understanding the user interaction with the developed OPAC website. Data is collected through testing to evaluate user interactions with the website. The testing is conducted to evaluate the effectiveness and quality of user interactions with the website, with the test results analyzed qualitatively to understand the performance and user satisfaction with the OPAC module. The contribution of this research lies in the development of library information systems, especially in improving accessibility and effectiveness of book title searches for users. It is hoped that by using the Knuth Morris Pratt (KMP) algorithm, the OPAC module website can provide accurate search results and enhance the user experience in searching for books at the Alma Ata University library in Yogyakarta